2021
DOI: 10.3390/cancers13246234
|View full text |Cite
|
Sign up to set email alerts
|

Locus-Specific Methylation of GSTP1, RNF219, and KIAA1539 Genes with Single Molecule Resolution in Cell-Free DNA from Healthy Donors and Prostate Tumor Patients: Application in Diagnostics

Abstract: The locus-specific methylation of three genes (GSTP1, RNF219, and KIAA1539 (also known as FAM214B)) in the blood plasma cell-free DNA (cfDNA) of 20 patients with prostate cancer (PCa), 18 healthy donors (HDs), and 17 patients with benign prostatic hyperplasia (BPH) was studied via the MiSeq platform. The methylation status of two CpGs within the same loci were used as the diagnostic feature for discriminating the patient groups. Many variables had good diagnostic characteristics, e.g., each of the variables GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…However, the authors have also shown that cfDNA methylation analysis alone is not sufficient for successful cancer detection. The reasons for the decrease in the effectiveness of PCR may be the methylation mode, when not all CpG dinucleotides in the promoter region are simultaneously methylated [ 37 ], as well as allele-specific methylation [ 43 ]. At the same time, some new approaches, such as the use of NGS sequencing targeting a specific locus make it possible to overcome such limitations [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the authors have also shown that cfDNA methylation analysis alone is not sufficient for successful cancer detection. The reasons for the decrease in the effectiveness of PCR may be the methylation mode, when not all CpG dinucleotides in the promoter region are simultaneously methylated [ 37 ], as well as allele-specific methylation [ 43 ]. At the same time, some new approaches, such as the use of NGS sequencing targeting a specific locus make it possible to overcome such limitations [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for the decrease in the effectiveness of PCR may be the methylation mode, when not all CpG dinucleotides in the promoter region are simultaneously methylated [ 37 ], as well as allele-specific methylation [ 43 ]. At the same time, some new approaches, such as the use of NGS sequencing targeting a specific locus make it possible to overcome such limitations [ 43 ]. It should be mentioned that the low level of aberrantly methylated DNA in cfDNA represents a serious limitation in all methods aimed at analyzing tumor DNA circulating in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, circGNB1 overexpression increased OA severity in the DMM mouse model, whereas circGNB1 silencing had the opposite effect. RNF219 (also known as C13orf7) plays a role in prostate tumors, 47 attention-deficit/hyperactivity disorder 48 and other diseases, 49 although its role in OA remains unclear. In this article, our results indicated that RNF219 expression was up-regulated in the cartilage of the medial tibial plateaus in older patients.…”
Section: Discussionmentioning
confidence: 99%
“…In our study it is blood and semen. Blood is commonly used in diagnostics but low in cfDNA concentration while semen is, partly, secreted from the prostate, and high in cfDNA concentrations [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, it is blood and semen. Blood is commonly used in diagnostics but low in cfDNA concentration while semen is, partly, secreted from the prostate and high in cfDNA concentrations [ 21 , 22 ]. Considering the variety of genetic alternations in PCa (113 mutations in 72 driver gene loci), we focused on epigenetic modifications which are restricted to promoters and retain specific patterns within the same cancer model [ 23–25 ].…”
Section: Discussionmentioning
confidence: 99%